Effect of fillers on the longevity of the plastic infused mining wire ropes - Devasahayam, Sheila; Sahajwalla, Veena; Michael Sng, Michael (2014)
Mining wire ropes (MWR) are subjected to continued bending, tensile stresses and fluctuating loads. Rope deterioration study is crucial for safe operating environment in open cut mines, better planning in terms of rope changes, resulting in reduced cost to production ratios. This study investigates why some MWR perform better than the others. Scanning electron microscope and Fourier Transform Infrared spectroscopy studies revealed the presence of kaolin as filler at the surface/interface of polymer component of better performing wire ropes and none in the ones that failed before its expected life expectancy. It is suggested kaolin reduces the incompatibility between PP and PE blend and the microstructure of the semi crystalline polymer matrices. Fracture toughness rendered by these fillers to the polymer matrix enhanced the mechanical performance of these ropes, by virtue of their ability to act as crack stoppers due to their smaller sizes.